Internet Addiction and Its Relationship with Depression and Academic Performance: A Cross-Sectional Study at a Medical School in Pakistan - Ansar, Farrukh; Ali, Waqar; Zareef, Adil; Masud, Noman; Zahab, Sawar; Iftekhar, Huma (International Journal of Medical Students, 2020)
Background: Excessive Internet use may induce depression, influence relationships, and decrease academic performance. There is scarce information about Internet addiction in Pakistan. This study aimed to determine prevalence of Internet addiction and its relationship with depression and academic performance. Methods: A study based on a self-administered survey was carried out at a medical school in Peshawar, Pakistan. Participants were medical students (MBBS) and a non-randomized convenience sampling technique was utilized for data collection. We collected demographic information, last professional exam score, Internet addiction, and depression scores using the Young’s Internet Addiction Test (YIAT) and the Beck’s Depression Inventory (BDI), respectively. The analysis included binomial 95% confidence intervals (95% CI) estimations and linear and logistic regressions to assess variables relations. Results: We analyzed responses from 231 participants (380 students approached and 250 responded: response rate=65.79%, 19 excluded), 64.07% were male and the age average was 21±2 years. Profound and slight addiction to the Internet was found in 9.09% (95%CI=5.71-13.56) and 41.99% (95%CI=35.55-48.64) of students, respectively. Frequency of depression (mild-severe) was 59.74% (95%CI=53.11-66.12). Levels of Internet addiction and depression were found associated after adjusting by sex and age (?=0.27, R2=0.03, p-value=0.009). Internet addiction (OR=0.54, 95%CI=0.2-1.49, p-value=0.23) and depression (OR=0.62, 95%CI=0.36-1.09, p-value=0.10) were not significantly associated with low grades after adjusting by sex and age. Conclusion: More than half of the students are having excessive Internet usage which could result in despondency and academic performance deterioration. Internet addiction should be considered an emerging challenge and appropriate mitigation measures should be taken opportunely.